2013
DOI: 10.1002/cssc.201300631
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Production Using Models of the Iron–Iron Hydrogenase Active Site Dispersed in Micellar Solution

Abstract: International audienceIron–thiolate complexes of the type [Fe2(μ-bdt)(CO)6−xP(OMe3)x] (bdt=S2C6H4=benzenedithiolate, x≤2) are simplified models of iron–iron hydrogenase enzymes. Recently, we have shown that these water-insoluble organometallic complexes, when included into micelles formed by sodium dodecyl sulfate (SDS), are good catalysts for the electrochemical production of hydrogen in aqueous solutions at pH<6. We herein report that the all-CO derivative [Fe2(μ-bdt)(CO)6] (1), owing to its comparatively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…[29] A higher efficiency of hydrogen production was achieveda t pH 11.0. This value is larger than the systems containing an iron-iron hydrogenaser edox catalyst with Fl as photosensitizer, [30] confirming the advantage of the supramolecular system for photocatalytic hydrogen production.C ontrol experiments revealed that the absence of any of these individual components resulted in no hydrogen production andt hat the artificial system did not functionw ell in the absence of light.T he reactions using the mononuclear tris(bipyridine)iron complex, which resembles the corner of the molecular cube as redox catalyst, produces only very small amounts (< 20 mLh ydrogen) under the same experimental conditions with same iron ion concentration. About 0.20 mL hydrogen productionw as achieved at ap Ho f1 1.0.…”
Section: Resultsmentioning
confidence: 92%
“…[29] A higher efficiency of hydrogen production was achieveda t pH 11.0. This value is larger than the systems containing an iron-iron hydrogenaser edox catalyst with Fl as photosensitizer, [30] confirming the advantage of the supramolecular system for photocatalytic hydrogen production.C ontrol experiments revealed that the absence of any of these individual components resulted in no hydrogen production andt hat the artificial system did not functionw ell in the absence of light.T he reactions using the mononuclear tris(bipyridine)iron complex, which resembles the corner of the molecular cube as redox catalyst, produces only very small amounts (< 20 mLh ydrogen) under the same experimental conditions with same iron ion concentration. About 0.20 mL hydrogen productionw as achieved at ap Ho f1 1.0.…”
Section: Resultsmentioning
confidence: 92%
“…Some of these homogeneous photocatalytic systems can operate very efficiently (in terms of number of catalytic cycles or turnover number (TON)) in organic or mixed aqueous-organic solvents. Those reaching a turnover number versus catalyst (TON Cat ) above 100 in fully aqueous solution were rare and limited to rhodium [36][37][38][39] and platinum [40] but, since two years, several examples with cobalt [41][42][43][44][45][46][47][48][49][50][51][52][53][54], iron [55][56][57][58] nickel [59] were reported. Developing H 2 -evolving photocatalytic systems functioning in pure water is essential for their coupling with water oxidation systems in photoelectrochemical water-splitting devices.…”
Section: Introductionmentioning
confidence: 98%
“…1 In this context, efficient photocatalytic production of dihydrogen (H 2 ) under visible-light irradiation, which is believed to be a convenient clean energy carrier for the future, is an important goal. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Those operating efficiently in fully aqueous solution were rare and limited to noble-metal based catalysts (rhodium and platinum) [22][23][24][25][26][27] until 2012, when several examples with cobalt, [28][29][30][31][32][33][34][35][36][37][38][39][40][41] iron [42][43][44][45] and nickel-based 46 catalysts were reported. Numerous photocatalytic systems in literature exhibit high activity in organic media or in mixtures of aqueous/organic solvents.…”
Section: Introductionmentioning
confidence: 99%